Simulation study of construction processes in repair and retrofitting of public housing - Lew, Vincent Wei Sern. (2008)
This dissertation is an attempt to apply construction simulation tools in project planning for public housing repair and retrofitting projects, or more commonly termed, upgrading projects. Critical activities within a typical upgrading project were identified. These were the production, erection, wet joint construction and architectural finishes works in the precast Space Adding Item (SAI).